Probing atom dynamics of excited Co-Mo-S nanocrystals in 3D - Fu-Rong Chen (Nature Portfolio, 2021)
The authors introduce an analytical approach for quantitative analysis of 3D atom dynamics during electron microscopy. They image a Co-Mo-S nanocrystal with 1.5 Å resolution, and observe chemical transformations caused by beam-stimulated vibrations.